Pengaruh Modal Usaha, Lokasi Usaha, Lama Usaha dan Teknologi Informasi terhadap Pendapatan Thrift Shop di Kota Surakarta - Alfrida Sekar Ayuningtyas; Arif Farida; Era Trianita Saputra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the influence of business capital, business location, length of business and information technology on thrift shop income in the city of Surakarta. This research uses quantitative methods and data collection methods through questionnaires. Sampling used a purposive sampling technique with a sample size of 97 respondents determined using the lemeshow formula. Data analysis techniques use data quality testing methods, classical assumption testing, multiple linear regression testing and hypothesis testing. Based on the results of the analysis, it proves that business capital, business location, length of business and information technology have a significant influence on thrift shop income in the city of Surakarta.